Fabrication of colorimetric textile sensor based on rhodamine dye for acidic gas detection - Park, Young Ki; Oh, Byeong M.; Jo, A. Ra; Han, Ji Hyeon; Lim, Jee Young; Oh, Hyun Ju; Lim, Seung Ju; Kim, Jong H.; Lee, Woo Sung (Polymers, 2020)
For the immediate detection of gaseous strong acids, it is advantageous to employ colorimetric textile sensors based on halochromic dyes. Thus, a rhodamine dye with superior pH sensitivity and high thermal stability was synthesized and incorporated in nylon 6 and polyester fabrics to fabricate textile sensors through dyeing and printing methods. The spectral properties and solubility of the dye were examined; sensitivity to acidic gas as well as durability and reversibility of the fabricated textile sensors were investigated. Both dyed and printed sensors exhibited a high reaction rate and distinctive color change under the acidic condition owing to the high pH sensitivity of the dye. In addition, both sensors have outstanding durability and reversibility after washing and drying.
Keywords: Acidic conditions; Gas detection; High thermal stability; pH sensitive; Polyester fabric; Rhodamine dyes; Spectral properties; Textile sensors; Dyeing; Gas detection; PH sensitive; Printing; Rhodamine dye; Textile sensor